Penerapan Absensi Berbasis Biometric dalam Disiplin Jam Kerja Pegawai Negeri Sipil (PNS) - Adiwidjaja, Ignatius; Kaurna, Elisabeth; Fithriana, Noora (Universitas Tribhuwana Tunggadewi, 2024)
Workers in an organization use attendance to indicate their presence or absence from work. This study aims to determine the use of biometrics in terms of the discipline of civil servant working hours, as well as supporting and inhibiting factors. The main informant is a BKD officer who is the attendance admin of the Sukun Village office based on biometrics, and the informant identification method is a snowball sampling approach. Data analysis includes data reduction, data presentation, drawing conclusions, and verification. The research results show that the Sukun Village, Malang City has involved the participation of unique biometric-based signs to implement the government authorities' plans to complete the work. The utilization of fingerprint participation empowers the grounded, precise and high-security use of government representative discipline during working hours. Absenteeism is a training exercise used by individual staff to indicate their presence or absence at work in the office. Variables supporting the implementation of biometric-based participation include the presence of biometric-based participation, the appropriateness of the time used is very good and the existence of a unique finger impression machine can help see employee delays which have a big impact on TPP. The use of biometric-based attendance is hampered by factors such as poor interference with the internet network which hinders the operation of information systems, and outdated equipment which often causes problems (errors).AbstrakPekerja dalam suatu organisasi menggunakan absensi untuk menunjukkan kehadiran atau ketidakhadiran mereka dari pekerjaan. Kajian ini bertujuan untuk mengetahui pemanfaatan biometrik dilihat dari disiplin jam kerja PNS, serta faktor pendukung dan penghambatnya. Informan utama adalah petugas BKD yang merupakan admin absensi kantor Kelurahan Sukun berdasarkan biometrik, dan metode identifikasi informan adalah dengan pendekatan snowball sampling. Analisis data meliputi reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi. Hasil penelitian menunjukkan bahwa Kelurahan Sukun Kota Malang telah melibatkan partisipasi tanda unik berbasis biometrik untuk melaksanakan rencana otoritas pemerintah untuk menyelesaikan pekerjaan. Pemanfaatan partisipasi sidik jari memberdayakan penggunaan disiplin perwakilan pemerintah yang membumi, tepat, dan aman tinggi selama jam kerja. Ketidakhadiran adalah pelatihan yang digunakan oleh individu staf untuk menunjukkan kehadiran atau ketidakhadiran mereka di tempat kerja di kantor. Variabel pendukung pelaksanaan partisipasi berbasis biometrik antara lain adanya partisipasi berbasis biometrik, kelayakan waktu yang digunakan sangat baik dan adanya mesin finger impression yang unik dapat membantu melihat keterlambatan pegawai yang sangat berpengaruh pada TPP. Penggunaan absensi berbasis biometrik terkendala oleh faktor-faktor seperti gangguan yang kurang baik pada jaringan internet yang menghambat pengoperasian sistem informasi, dan peralatan yang sudah ketinggalan zaman yang sering terjadi masalah (error).